Rational design of phenothiazinium derivatives and photoantimicrobial drug discovery. (January 2017) - Wainwright, Mark; McLean, Andrew
Abstract: While the model for conventional antimicrobial drug discovery is based securely on singular modes and sites of action, those associated with phenothiazinium photoantimicrobial candidates are both multifactorial and variable, resulting from oxidation events due to reactive oxygen species (ROS). The effective counteraction of such species and their variable targets is clearly problematic from the point of view of microbial resistance mechanism development, and offers considerable opportunity for the use of these agents in local infection control. However, this also means that drug development cannot be carried out using similar methods to those employed for conventional agents. Furthermore, these multifactorial photoantimicrobial agents are truly broad-spectrum since they are active against bacteria, fungi, viruses and protozoa, again at variance with the targeting of conventional, single-class antimicrobials. This review concentrates on the use of the phenothiazinium class as exemplar photoantimicrobials, due to their pre-eminence in the field and considers the various criteria required for successful activity against microbes. These include alicyclic fusion, chalcogen substitution, benzo[ a ] fusion and the heavy atom effect, to decrease aggregation, improve ROS production and extend absorption wavelength, as well as conventional approaches, such as increasing cationic character to improve microbial selectivity/targeting. Highlights: Functionalisation of phenothiazinium salts increases photodynamic activity. Aromatic/aliphatic ring fusion produces longer wavelength absorption. Heavy atom inclusion increases singlet oxygen production. Increasing cationic character improves photoantimicrobial action. Very broad-spectrum activity includes Gram ± bacteria, fungi, viruses and protozoa.